2017
DOI: 10.1002/jmri.25815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid atherosclerotic plaque surface characteristics utilizing simultaneous noncontrast angiography and intraplaque hemorrhage (SNAP) technique

Abstract: Purpose To evaluate the feasibility of the Simultaneous Noncontrast Angiography and intraPlaque hemorrhage (SNAP) technique in identification of carotid plaque surface characteristics compared with the conventional multicontrast vessel wall imaging protocol. Materials and Methods Thirty symptomatic patients with carotid plaque were recruited and underwent carotid artery magnetic resonance imaging (MRI) (3.0T) using a conventional multicontrast protocol and SNAP sequence. As an intrinsic multicontrast sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…CA can be detected by a hypointense signal in all contrast weightings and can be delineated more clearly using 3D multi-contrast imaging, as indicated in Figure 6. Recent studies showed that SNAP imaging, with high reproducibility, agreed well with conventional reference multi-contrast imaging in identification of CA (24), which was also illustrated in another representative case (Figure 6). As for LRNC detection, T1 and T2 imaging were mainly used.…”
Section: Discussionsupporting
confidence: 71%
“…CA can be detected by a hypointense signal in all contrast weightings and can be delineated more clearly using 3D multi-contrast imaging, as indicated in Figure 6. Recent studies showed that SNAP imaging, with high reproducibility, agreed well with conventional reference multi-contrast imaging in identification of CA (24), which was also illustrated in another representative case (Figure 6). As for LRNC detection, T1 and T2 imaging were mainly used.…”
Section: Discussionsupporting
confidence: 71%
“…3D VFA‐FSE has also been proposed, exploiting the intrinsic flow sensitivity of this technique for black‐blood contrast 89, 90 . A recent technique permits 3D acquisition and simultaneous depiction of the vessel wall and the vascular lumen using a combined bright‐ and black‐blood imaging sequence 91 . Modern black‐blood MRI techniques of the carotid bifurcation are highly accurate for identifying carotid atherosclerosis, including intraplaque hemorrhage 92,93 and patients at increased risk for stroke 94–96 …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…3) to characterize features of plaque vulnerability such as intra-plaque hemorrhage IPH, LRNC, and the status of the FC. 26 MR allows for the accurate distinction of plaque components 27 such as the LRNC, fibrous tissue, and IPH exploiting their different signal properties. While the identification of calcified components can be more challenging compared to CT, MR still offers usually good results.…”
Section: Mrmentioning
confidence: 99%